2022
DOI: 10.4274/tjod.galenos.2022.49696
|View full text |Cite
|
Sign up to set email alerts
|

Superior hypogastric plexus (SHP) block during minimally invasive hysterectomy: A systematic review

Abstract: To systematically summarize the efficacy and safety of superior hypogastric plexus (SHP) block versus no SHP block among patients undergoing minimally invasive hysterectomy (MIH). Five information sources were screened from inception until 04.04.2022 and comprised the Cochrane Central Register of Controlled Trials, PubMed, Embase, Scopus, and Web of Science. The inclusion criteria comprised (i) patients: individuals undergoing MIH, (ii) intervention: SHP block, (iii) Comparator: no SHP block, (iv) Outcomes: po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Alomar and colleagues [ 34 ] examined the role of SHP block versus none during minimally invasive hysterectomy. The authors included three studies and concluded the morbidity-free and satisfactory postoperative pain-reliving and opioid-free effects of SHP block.…”
Section: Discussionmentioning
confidence: 99%
“…Alomar and colleagues [ 34 ] examined the role of SHP block versus none during minimally invasive hysterectomy. The authors included three studies and concluded the morbidity-free and satisfactory postoperative pain-reliving and opioid-free effects of SHP block.…”
Section: Discussionmentioning
confidence: 99%